Obtaining a Foundation for Nursing Care at the Time of Patient Admission: A Grounded Theory Study - Jansson, Inger (Bentham Open, 2009)
The nursing process can be viewed as a problem-solving model, but we do not know whether use of the whole process including care plans with interventions based on nursing diagnoses improves nurses’ ability to carry out assessments. Therefore, the aim of this study was to illuminate and describe the assessment and decision-making process performed by nurses who formulated individual care plans including nursing diagnosis, goals and interventions or who used standardized care plans when a patient was admitted to their ward for care, and those who did not. Data collection and analysis were carried out by means of Grounded theory. Nurses were observed while assessing patients, after which they were interviewed. The main concern of all nurses was to obtain a foundation for nursing care based on four strategies; building pre-understanding, creating a caring environment, collecting information on symptoms and signs and performing an analysis from different perspectives. It appeared that the most important aspect for nurses who did not employ care plans was the medical reason for the patient’s admission. The nurses who employed care plans discussed their decisions in terms of nursing problems, needs and risks. The results indicate that nurses who formulated care plans were more aware of their professional role.